Racism Seen From a Contextual Biblical Ethical Perspective - Wahyoe Rita Wulandari (Green Publisher Indonesia, 2022)
The main issue discussed is about racism. While the formal object is the contextual biblical ethics. The biblical interpretation is limited to the response of Lord Jesus to racism, creation and the genealogy of humankind that made by one blood (Adam). From this genealogy we realize that all humans have a conscience given by the LORD God. A conscience or common sense that gives everyone to do something fairly. The justice of the conscience of the Indonesian nation is called